Iodine-125 brachytherapy in inoperable duodenal papilla carcinoma: a case report series - Zhang, Yue; Xu, Shangbin; Xu, Jing; Wu, Shen; Yao, Wenyi; Lu, Shengying; Zhang, Guangtao; Chen, Tingsong (Frontiers in Oncology, 2024)
Background Duodenal papilla carcinoma (DPC) is a rare malignancy often diagnosed at an advanced stage. When surgery is not feasible in localized disease due to advanced age or comorbidities, there remains no consensus on optimal management for these patients. Case summary This case series details the therapeutic outcomes of 125I seed implantation in two elderly patients with DPC. A notable tumor reduction was achieved within two months after implantation. Furthermore, both patients demonstrated radiological tumor response and survived for over six months following the initial 125I seed treatment, marking the first reported instance of 125I seed implantation to effectively control DPC. Conclusion The anti-tumor activity of 125I seed implantation in the reported two cases of DPC underscores its potential as a viable treatment option for inoperable localized DPC.